Apitherapy for Parkinson's Disease: A Focus on the Effects of Propolis and Royal Jelly. (17th October 2020) - Ali, Amira Mohammed; Kunugi, Hiroshi
Abstract : The vast increase of world's aging populations is associated with increased risk of age-related neurodegenerative diseases such as Parkinson's disease (PD). PD is a widespread disorder characterized by progressive loss of dopaminergic neurons in the substantia nigra, which encompasses a wide range of debilitating motor, emotional, cognitive, and physical symptoms. PD threatens the quality of life of millions of patients and their families. Additionally, public welfare and healthcare systems are burdened with its high cost of care. Available treatments provide only a symptomatic relief and produce a trail of noxious side effects, which increase noncompliance. Hence, researchers have recently focused on the use of nutraceuticals as safe adjunctive treatments of PD to limit its progress and associated damages in affected groups. Propolis is a common product of the beehive, which possesses a large number of therapeutic properties. Royal jelly (RJ) is a bee product that is fed to bee queens during their entire life, and it contributes to their high physical fitness, fertility, and long lifespan. Evidence suggests that propolis and RJ can promote health by preventing the occurrence of age-related debilitating diseases. Therefore, they have been used to treat various serious disorders such as diabetes mellitus, cardiovascular diseases, and cancer. Some evolving studies used these bee products to treat PD in animal models. However, a clear understanding of the collective effect of propolis and RJ as well as their mechanism of action in PD is lacking. This review evaluates the available literature for the effects of propolis and RJ on PD. Whenever possible, it elaborates on the underlying mechanisms through which they function in this disorder and offers insights for fruitful use of bee products in future clinical trials.